Стилистика в аспекте преподавания русского языка как иностранного - ЛЫСАКОВА, ИРИНА П. (Stylistyka, 2021)
Russian as а Foreign Language This article analyses functional particularities of teaching stilistics in the aspect of Russian as а foreign language. lt proves that the differentiation of speech actions in communicational teaching supposes the knowledge of stylistic variations of vocabulary and syntactic structures, because "communicative competence" includes the mastering of speech patterns in different social situations. So it is necessary to start the introduction of some stylistic elements in the elementary stage of teaching Russian as а foreign language.